(untitled) (Journal of Computational Mathematics, 2018)
Taking h_m as the mesh width of a curved edge Γ _m (m=1,...,d ) of polygons and using quadrature rules for weakly singular integrals, this paper presents mechanical quadrature methods for solving BIES of the first kind of plane elasticity Dirichlet problems on curved polygons, which possess high accuracy O(h_0^3) and low computing complexities. Since multivariate asymptotic expansions of approximate errors with power h_i^3 (i=1,2,...,d) are shown, by means of the splitting extrapolations high precision approximations and a posteriori estimate are obtained.